PERSPEKTIF FILSAFAT AGAMA TENTANG KERUKUNAN BERAGAMA - Theguh Saumantri (UIN Sunan Kalijaga Yogyakarta, 2023)
Indonesia, as a country rich in cultural, ethnic, and religious diversity, has faced complex challenges in achieving social harmony and inter-religious harmony. Over time, the complexity of religious diversity has given rise to a number of problems, including inter-religious conflicts, insults, and a lack of understanding of the principles of religious harmony. This study aims to enrich the understanding of the concept of religious harmony from the perspective of religious philosophy as well as identify the contribution of religious philosophy to enriching the understanding of religious harmony in the context of religious diversity in Indonesia. This research uses a descriptive research method with a phenomenological approach. Based on the analysis conducted, it can be interpreted that religious harmony is a fundamental concept in the lives of religion and society. This relates to the formation of an attitude of tolerance, mutual respect, and understanding differences. In the philosophy of religion, religious harmony can be built through Synergizing Religious pluralism, involving Inter-Religious Dialogue, and implementing Religious Ethics and Morality holistically. Keywords: Religious Harmony, Religious Philosophy, Tolerance. Abstrak Indonesia, sebagai negara yang kaya akan keberagaman budaya, etnis, dan agama, telah menghadapi tantangan kompleks dalam mencapai harmoni sosial dan kerukunan antarumat beragama. seiring berjalannya waktu, kompleksitas keberagaman agama telah menimbulkan sejumlah permasalahan, termasuk konflik antaragama, diskriminasi, dan kurangnya pemahaman tentang prinsip-prinsip kerukunan beragama. Penelitian ini bertujuan untuk memperkaya pemahaman tentang konsep kerukunan beragama dalam perspektif filsafat agama, serta mengidentifikasi kontribusi filsafat agama dalam memperkaya pemahaman tentang kerukunan beragama dalam konteks keberagaman agama di Indonesia. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan pendekatan fenomenologi. Berdasarkan analisis yang dilakukan, dapat disimpulkan bahwa kerukunan beragama merupakan konsep fundamental dalam kehidupan beragama dan masyarakat. Hal ini berkaitan dengan terbentuknya sikap toleransi, saling menghormati, dan memahami perbedaan. Dalam filsafat agama, kerukunan beragama dapat dibangun melalui Mensinergikan Pluralitas Agama, melibatkan Dialog Inter-Religius, serta menerapkan Etika dan Moralitas Agama secara holistik. Kata kunci: Kerukunan Beragama, Filsafat Agama, Toleransi.